Likely Impacts of Climate Change on forest Fires and Adaptation Strategies - Gera, Mohit (Indian Forester, 2017)
Forest fires devastate forests that provide livelihood opportunities to millions of people around the world, besides emitting green house gases responsible for global warming. They are also detrimental to wildlife habitat and adversely impact ecotourism on which local communities depend. On the other hand, forest fire as a natural process helps forests by promoting flowering, branching and seedling establishment, besides aiding natural regeneration. The heating of the forest floor also result in beneficial microbial activity, and hasten decaying processes useful for the forest vegetation. In the background of changing climate, the recent global level studies are indicating a large increase in forest fires, which are projected to be higher by 38% over the next 30 years and 62% by the end of the century. The evidences of enhanced forest fires from around the world are also supporting these projections. The major forest types vulnerable to enhanced forest fires in India are the Tropical Dry Deciduous Forests, Tropical Dry Evergreen Forests, Tropical Thorn Forests and Sub-tropical Pine Forests, besides several others. The paper discusses the likely impacts of climate change on forest fires and ensuing challenges in management of forests. The adaptation and mitigation strategies to deal with the increasing forest fires are also suggested.